Movices architecture for meliponiculture diagnostic application system development - Mohd Yasar, Izatul Lail (2021)
Stingless beekeeping or meliponiculture is a growing phenomenon in Malaysia. It has a bright prospect in the agriculture sector where farmers can generate high income from it. Stingless beekeepers currently face problems in rehabilitating weakened stingless bee colonies, which they failed to rehabilitate most of these colonies. It is vital to have effective aids to help them to rehabilitate the weakened colonies. Hence, this study aimed to determine an appropriate borescope-based diagnostic application system, Dr. Kelulut, to rehabilitate domesticated stingless bee colonies in Malaysia. Due to this, an investigation on the effectiveness of weakened colonies rehabilitation in Malaysia was conducted. Interviews, nest inspection experiments and the development of Dr. Kelulut were carried out to achieve the study objectives. The Model-View-Controller (MVC) framework for expert system (MoViCES) architecture had been developed and used for Dr. Kelulut. This expert system verified the usability of MoViCES architecture. The system's structure can be illustrated in one diagram instead of two different diagrams from this architecture. The study finds that the effective technique for stingless bee hive inspection using a borescope is minimal surgery. Any symptoms found from the inspection can be diagnosed through Dr. Kelulut. Based on correctness evaluation, the diagnosis function of Dr. Kelulut is 81.7%. It shows that this system is most of the time identifying the colony problem correctly. The study concludes that the MoViCES architecture is useful in expert system development. The borescope inspection technique and Dr. Kelulut are effective combination diagnostic tools for rehabilitating domesticated stingless bee colonies in Malaysia. By using the combination tool, stingless beekeepers can prevent the stingless bee colonies from collapsing. Further, the weakened stingless bee colonies can be effectively rehabilitated. Therefore, it is highly suggested that the combination of the inspection technique and Dr. Kelulut should be introduced to the stingless beekeepers in Malaysia.